CH3NH3PbI3 based solar cell: modified by antisolvent treatment - Nandi, P.; Giri, C.; Bansode, U.; Topwal, D. (AIP Conference Proceedings, 2017)
Solar cells based on new class of organic inorganic hybrid perovskite CH3NH3PbI3 were prepared by Ethyl acetate (EA); antisolvent treatment for the first time. This treatment results in new morphology for CH3NH3PbI3 thin film. FESEM image shows microrod type structures of CH3NH3PbI3 after EA antisolvent treatment. Energy band diagram was constructed using photoluminescence and photoemission studies. A better power conversion efficiency was achieved in EA treated film compare to without EA treated film.
Keywords: CH3NH3PbI3; Perovskite solar cell